Violence an interdisciplinary approach to causes, consequences, and cures - Lee, Bandy X. 1970- (Wiley-Blackwell, 2019)
"A comprehensive overview of the integrative study of violence Violence continues to be one of the most urgent global public health problems that contemporary society faces. Suicides and homicides are increasing at an alarming rate, particularly in younger age groups and lower-income countries. Historically, the study of violence has been fragmented across disparate fields of study with little cross-disciplinary collaboration, thus creating a roadblock to decoding the underlying processes that give rise to violence and hindering efforts in research and prevention. Violence: An Interdisciplinary Approach to Causes, Consequences, and Cures assembles and organizes current information into one comprehensive volume, introducing students to the multiple sectors, disciplines, and practices that collectively comprise the study of violence. This innovative textbook presents a unified perspective that integrates the sociological, biological, politico-economic, structural, and environmental underpinnings of violence. Each chapter examines a distinct point of learning, beginning with an overview of the content and concluding with discussion questions and an analytical summary. The chapters focus on key domains of research encouraging interdisciplinary investigation and helping students to develop critical analytical skills and form their own conclusions. Fills a significant gap in the field by providing a coherent text that consolidates information on the multiple aspects of violence Examines current legal, medical, public health, and policy approaches to violence prevention and their application within a global context Illustrates how similar causes of violence may have dissimilar manifestations Presents a multidisciplinary examination of the symptoms and underlying processes of violence Offers a thorough yet accessible learning framework to undergraduate and graduate students without prior knowledge of the study of violence More than just an accumulation of facts and data, this essential text offers a broad introduction to a thinking process that can produce rigorous scholarship across disciplines and lead to a deeper understanding of violence in its many forms. "--Provided by publisher.